A Short Essay: High Dose Vitamin D Supplementation Reduces Medical Malpractice Lawsuits. - Matthews, Leslie (Medical Research Archives, 2016)
Background : Vitamin D supplementation has been shown to decrease hospital and ICU length of stays, hospital costs, mortality rates, and complications such as myocardial infarctions, infections, and narcotic use. Vitamin D supplementation direct and indirect effects upon medical malpractice lawsuits has been previously unknown. Hypothesis : We hypothesize that aggressive vitamin D supplementation would reduce medical malpractice lawsuits both directly and indirectly saving hospitals and insurance companies millions of dollars. Methods : We did a retrospective study reviewing the trauma registry of Morehouse 6, 200 trauma patients from 1995-2016 at a urban Level I trauma center. Vitamin D supplementation was started in 2008. We identified several malpractice lawsuits from 1995- February 2007.  The following total amount was paid out from 1995- February 2007 ($26,000,000.00). There have been zero lawsuits since 2007. Results : The total paid out from 1995- February 2007 was $26,000,000.00 for trauma lawsuits and zero dollars from after February 2007-2015 for a p-value of P<0.0001 Conclusion : We conclude since vitamin D decreases mortality rates, hospital and ICU length of stays, and complications rates from chronic diseases that the direct and indirect effects of aggressive vitamin D supplementation would be decreased medical malpractice lawsuits. Further studies are needed.